Epidural analgesia in labour and its obstetric outcome - Lakshmi, Srujana S. N.; R., Sheela S.; N., Kiran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Labour is a natural phenomenon which produces intolerable pain that requires effective methods for pain relief which is often challenging and complex task without regional analgesia. Epidural analgesia is most widely accepted method used to reduce labour pain. Aims and objectives were assessment of epidural analgesia in pain relief during labour, duration of different stages of labour, maternal and foetal outcome. Methods: This study was a prospective observational study conducted at RL Jalappa Hospital, Kolar from January 2020 to June 2021. 40 women admitted for normal vaginal delivery opting labour analgesia were studied. Data collected was entered in Microsoft excel spread sheet and results were analysed. Results: The mean duration of first stage of labour was 153 minutes, mean duration of second stage was 30 minutes, and mean duration of third stage was 12 minutes. During first stage of labour, 20 women (52%) had no pain, 12 women (31%) had mild pain and 6 women (15%) had moderate pain. During second stage of labour, 16 women (42%) had mild pain, 15 women (39%) had no pain and 7 women (18%) had moderate pain. During third stage of labour, 30 women (78.9%) had no pain and 8 women (21%) had mild pain. The mean Apgar score of all babies at 1 minute was 7/10 and 5 minute was 9/10. Conclusions: Epidural analgesia is a safe and effective technique during labour and provides significant pain relief with excellent patient satisfaction.